It can't be true! 2 - Star, Fleur, 1974-; Parrish, Margaret (London ; New York : DK, 2016)
Presents surprising facts about the world, including the size of the largest giant squid, how far a person walks in a lifetime, and what is the hottest chili pepper.
Planet Earth and beyond -- The natural world -- The human world -- Feats of engineering.
Includes index.
STEAM collection. Some copies purchased with funds from the Corvallis Public Schools Foundation.
Keywords: Curiosities and wonders -- Juvenile literature; Curiosities and wonders